Defisit dan Surplus Dampak Sistem INA CBG’S : Studi Kasus Pembiayaan Pasien Jiwa - Harjanti, Harjanti; Kelmaskosu, Anna Yolanda (Lembaga Penerbitan Universitas Esa Unggul, 2025)
Abstract The Indonesian Case-Base Groups (INA-CBG’s) serve as the primary instrument for determining reimbursement rates for National Health Insurance (JKN) patients based on clinical diagnoses and procedures. Initial findings at RSJD dr. Arif Zainudin in December 2022 indicated that hospital charges surpassed the INA- CBG’s benchmarks, leading to a deficit of IDR 3,685,862.00. This study evaluates the fiscal implications—specifically surpluses and deficits—of INA- CBG’s tariff implementation on psychiatric care financing at RSJD dr. Arif Zainudin Surakarta. Adopting a qualitative descriptive approach, data were gathered through in-depth interviews and direct observation. Analysis of the 2023 claim data revealed a significant positive variance of IDR 175,474,339.00. This surplus offers the hospital an opportunity for cross-subsidization and service quality enhancement. However, the unique clinical profile of psychiatric patients often leads to discrepancies between standardized rates and actual expenditures, especially in long-stay cases. To mitigate financial risks, the hospital has integrated Clinical Pathways, service standardization, and rigorous cost monitoring. The study concludes that the fluctuating financial outcomes of INA-CBG’s implementation necessitate strategic cost-control mechanisms aligned with psychiatric care policies to ensure institutional sustainability. Keywords: INA CBG’s, financing system, mental illness, national health insurance Abstrak Indonesia Case Base Groups (INA CBG’s) merupakan suatu instrumen yang dimanfaatkan dalam penentuan biaya perawatan pasien didasarkan pada diagnosis dan tindakan untuk pasien JKN. Hasil survei penelitian yang dilakukan di RSJD dr. Arif Zainudin dengan data klaim BPJS Desember 2022 diketahui tarif rumah sakit lebih besar dari tarif INA CBG’s sehingga terjadi defisit pada rumah sakit sebesar Rp 3.685.862,00. Tujuan untuk mengetahui surplus dan defisit dampak implementasi tarif INA CBG’s pada pembiayaan pasien jiwa di RSJD dr. Arif Zainudin Surakarta. Metode penelitian deskriptif dengan pendekatan kualitatif. Pengumpulan data menggunakan 2 teknik yaitu in depth interview dan observasi. Hasil analisis data klaim tahun 2023 menunjukkan adanya selisih positif sebesar Rp 175.474.339,00,. Adanya selisih ini dapat dimanfaatkan oleh Rumah Sakit untuk subsidi silang dan peningkatan mutu pelayanan. Karakterisitik pasien jiwa yang berbeda menimbulkan potensi ketidaksesuaian tarif INA CBG’s dan tarif riil terkhusus untul kasus dengan lama dirawat yang panjang. Penerapan clinical pathway, standarisasi pelayanan kasus jiwa dan monitoring biaya merupakan upaya pengendalian biaya dalam implementasi INA CBG’s. Dapat disimpulkan bahwa defisit dan surplus implementasi tarif INA CBG’s menyebabkan rumah sakit mengalami keuntungan dan juga kerugian pada pasien jiwa, maka rumah sakit perlu adanya pengendalian biaya kesehatan sesuai kebijakan pelayanan pasien jiwa. Kata Kunci: INA CBG’s, sistem pembiayaan, pasien jiwa, jaminan kesehatan nasional